Development prospectus, Richmond Street Complex. - Government of the Republic Trinidad and Tobago. Ministry of Planning and Mobilization. (Town and Country planning Division., 2011)
Discusses the development of a site in the Central Business District of Port-of-Spain at Richmond Street for various uses, and includes discussion of the legal framework, requests for proposals and evaluation procedures.
Keywords: Physical planning – Port of Spain, Urban planning, Urban development - Central business districts, Infrastructure – Port of Spain, Richmond Street Complex